Protein–Protein Interaction between Surfactant Protein D and DC-SIGN via C-Type Lectin Domain Can Suppress HIV-1 Transfer - Eswari Dodagatta-Marri; Daniel A. Mitchell; Hrishikesh Pandit; Archana Sonawani; Valarmathy Murugaiah; Susan Idicula-Thomas; Béatrice Nal; Béatrice Nal; Maha M. Al-Mozaini; Anuvinder Kaur; Taruna Madan; Uday Kishore (Frontiers in Immunology, 2017)
Surfactant protein D (SP-D) is a soluble C-type lectin, belonging to the collectin (collagen-containing calcium-dependent lectin) family, which acts as an innate immune pattern recognition molecule in the lungs at other mucosal surfaces. Immune regulation and surfactant homeostasis are salient functions of SP-D. SP-D can bind to a range of viral, bacterial, and fungal pathogens and trigger clearance mechanisms. SP-D binds to gp120, the envelope protein expressed on HIV-1, through its C-type lectin or carbohydrate recognition domain. This is of importance since SP-D is secreted by human mucosal epithelial cells and is present in the female reproductive tract, including vagina. Another C-type lectin, dendritic cell (DC)-specific intercellular adhesion molecule-3-grabbing non-integrin (DC-SIGN), present on the surface of the DCs, also binds to HIV-1 gp120 and facilitates viral transfer to the lymphoid tissues. DCs are also present at the site of HIV-1 entry, embedded in vaginal or rectal mucosa. In the present study, we report a direct protein–protein interaction between recombinant forms of SP-D (rfhSP-D) and DC-SIGN via their C-type lectin domains. Both SP-D and DC-SIGN competed for binding to immobilized HIV-1 gp120. Pre-incubation of human embryonic kidney cells expressing surface DC-SIGN with rfhSP-D significantly inhibited the HIV-1 transfer to activated peripheral blood mononuclear cells. In silico analysis revealed that SP-D and gp120 may occupy same sites on DC-SIGN, which may explain the reduced transfer of HIV-1. In summary, we demonstrate, for the first time, that DC-SIGN is a novel binding partner of SP-D, and this interaction can modulate HIV-1 capture and transfer to CD4+ T cells. In addition, the present study also reveals a novel and distinct mechanism of host defense by SP-D against HIV-1.